2014
DOI: 10.1007/s10903-014-0131-7
|View full text |Cite
|
Sign up to set email alerts
|

Examining Pre-migration Health Among Filipino Nurses

Abstract: The healthy immigrant hypothesis asserts that immigrants arrive in the receiving country healthier than same race/ethnic counterparts born there. Contemporary research, however, has not evaluated pre-migration health among migrants, nor has explicitly considered comparisons with non-migrants in the country of origin. Pre-migration health was examined among 621 Filipino nurses, including self-reported physical health, mental health, health behaviors, and social stress. Measures were compared by intention to mig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 67 publications
0
4
0
Order By: Relevance
“…Other research with Filipino home-health workers and those employed in nursing homes and assisted living facilities underscores exploitative employment conditions (e.g., irregular or lack of mandated rest and meal breaks), lack of safety protections (e.g., limited personal protective equipment, or PPE), risk of physical injury on the job, and lack of health insurance or limited access to medical care ( 15 ) that existed prior to the pandemic. Many of the Filipino workers in healthcare and caregiving are migrants ( 16 ), with research showing a positive association between job-related stressors and chronic health conditions ( 17 ) as well as a link between job dissatisfaction and psychological distress ( 18 ) among Filipino migrants overall. Despite the mounting evidence exploring occupational stressors and their effects on health, few studies have examined the experiences of Filipino American frontline workers employed across diverse industries during the pandemic ( 3 , 19 ).…”
Section: Introductionmentioning
confidence: 99%
“…Other research with Filipino home-health workers and those employed in nursing homes and assisted living facilities underscores exploitative employment conditions (e.g., irregular or lack of mandated rest and meal breaks), lack of safety protections (e.g., limited personal protective equipment, or PPE), risk of physical injury on the job, and lack of health insurance or limited access to medical care ( 15 ) that existed prior to the pandemic. Many of the Filipino workers in healthcare and caregiving are migrants ( 16 ), with research showing a positive association between job-related stressors and chronic health conditions ( 17 ) as well as a link between job dissatisfaction and psychological distress ( 18 ) among Filipino migrants overall. Despite the mounting evidence exploring occupational stressors and their effects on health, few studies have examined the experiences of Filipino American frontline workers employed across diverse industries during the pandemic ( 3 , 19 ).…”
Section: Introductionmentioning
confidence: 99%
“…For example, Breslau and Colleagues (2011) found that Mexican migrants were more likely to exhibit greater anxiety and mood disorders compared to non-migrants in Mexico. Another study among Filipino nurses found depressive symptoms to be higher among those intending to migrate to the U.S. ( de Castro et al., 2015 ). This may be due to additional stressors and pressures stemming from their occupation and other employment factors that may be unique to this group of migrants.…”
Section: Discussionmentioning
confidence: 99%
“… Akresh and Frank (2008) found differences in health selection by geographic area of residence and across countries and specifically, Mexican immigrants were least likely to exhibit health selection. In another study, de Castro and Colleagues (2015) found that Filipino nurses who were intending to migrate to the U.S. had worse mental health outcomes than those residing in the Philippines. This finding may be due to the fact that Filipino nurses seeking employment opportunities abroad (e.g., Canada, U.S.) for greater financial security and improved working conditions ( Ronquillo et al., 2011 ).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Therefore, pre-migration individuals' alcohol and other drug use norms and alcohol and other drug use should be explored as a part of a comprehensive innovative preventive approach (Salas-Wright & Schwartz, 2019). An analysis of individual health-related behavior before leaving may significantly contribute to a deeper understanding of the healthy immigrant hypothesis (De Castro, Gee, Fujishiro et al, 2015). This study will limit its focus on behaviors concerning alcohol use and smoking.…”
Section: Introductionmentioning
confidence: 99%